Penerapan Metode MOOSRA dan MOORA dalam Keputusan Pemilihan Produk Asuransi Terbaik - Suryanto, Andik Adi; Alam, Sitti Nur; Widjaja, Warkianto; Wijaya, Hamid; Adhicandra, Iwan (Building of Informatics, Technology and Science (BITS), 2023)
At present, public opinion regarding the selection of insurance products is very low because people still do not understand enough to insure themselves against a product that will guarantee their necessities of life. Especially now that there are so many insurance products out there, it's likely that people don't want to register for insurance. Therefore, people must be careful in choosing an insurance product so that it fits what they want. The Decision Support System is a computerized system and is designed to assist management in making decisions to solve semi-structured and unstructured problems so that the decision-making process can be of higher quality. This application that will be made is an application that is guided by the MOORA method. Therefore, an application that is guided by the MOORA method is very suitable for calculating insurance product selection. From the results of our research we conducted the MOOSRA and MOORA methods for selecting insurance products easier and more precise than the manual work method. applying the MOORA method produces an alternative A5, namely Prudential with a value of 0.217 as the best alternative.